4-(Hydroxymethyl)catechol Extracted From Fungi in Marine Sponges Attenuates Rheumatoid Arthritis by Inhibiting PI3K/Akt/NF-κB Signaling - Lee, Jong Y.; Kim, Geum J.; Choi, Jin K.; Choi, Young-Ae; Jeong, Na-Hee; Park, Pil-Hoon; Choi, Hyukjae; Kim, Sang-Hyun (Frontiers in Pharmacology, 2018)
Rheumatoid arthritis (RA) is a progressive autoimmune disease specific to synovial joints; it causes joint damage and other systemic abnormalities, thereby leading to physical disability and early mortality. Marine sponge-derived fungi, Pestalotiopsis sp., secrete immunosuppressive compounds in the culture broth. In the present study, we isolated 4-(hydroxymethyl)catechol (4-HMC) from these fungal species, and evaluated its anti-RA effects using a murine collagen-induced arthritis (CIA) model and tumor necrosis factor-α-stimulated human RA synovial fibroblasts. Oral 4-HMC administration decreased the clinical arthritis score, paw thickness, histologic and radiologic changes, and serum IgG1 and IgG2a levels. It prevented the proliferation of helper T (Th) 1/Th17 CD4+ lymphocytes isolated from inguinal lymph nodes, thereby reducing inflammatory cytokine production in CIA mice. It decreased the expression of inflammatory mediators, including cytokines and matrix metalloproteinases (MMPs), both in vitro and in vivo. We observed that 4-HMC suppresses Th immune responses and MMP expression to inhibit inflammatory cytokine production in human RA synovial fibroblasts by modulating the PI3K/Akt/NF-kappaB pathway. These results verify the anti-RA potential of 4-HMC.